ANALISIS HUBUNGAN PROMOSI TERHADAP VOLUME PENJUALAN SEMEN TONASA DI WILAYAH PASAR KALIMANTAN TIMUR: ANALYSIS OF PROMOTION RELATIONSHIP ON TONASA CEMENT SALES VOLUME IN EAST KALIMANTAN MARKET AREA - Rego Devila (Yayasan Education and Social Center, 2023)
This study aims to determine the effect of promotion on sales volume. This research is causal research, where there is a relationship between promotion and sales volume of PT. Semen Tonasa in the East Kalimantan region. The population in this study are shops located in the East Kalimantan market area. Sampling was carried out by purposive sampling, with a sample of 200 shop respondents. The type of data used in this research is primary data. The data collection method used was a survey by distributing questionnaires to respondents. Analysis of research data using simple regression analysis using the SPSS version 25.00 program. The results of the study show that promotion has a significant effect on sales volume